The Relationship Between Stress and Insomnia In Students Class Of 2019 Which are Working Thesis at The Faculty Of Medicine, YARSI University and Review according to an Islamic Perspective - Annisa Amelia; Eko Purwanto; Firman Arifandi (Junior Medical Journal, 2022)
Thesis is a final task that is not easy and is often faced with various kinds of difficulties. This difficulty makes students become stressed and then has the potential to cause disturbances such as sleep disturbances or insomnia. The purpose of this study was to determine the relationship between stress levels and the incidence of insomnia in YARSI University Medical Faculty students class of 2019 who are working on their thesis and review on Islam. This study used an analytical method with a cross-sectional approach, and the sample selection used a simple random sampling technique. The number of samples used is 70 respondents. Data collection was carried out using a questionnaire. Data were analyzed by Pearson correlation test. The results showed that there was a significant correlation between stress levels and insomnia in class 2019 students with the results r = 0.380 and p = 0.001. It can be concluded that there is a relationship between stress levels and the incidence of insomnia in YARSI University Medical Faculty students in the class of 2019 who are working on their thesis.